FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN DIGITALISASI PADA MANAJEMEN USAHA BAGI PELAKU UMKM - Rahmad Kurniawan; Azizatur Rosyida; Smita Catur Sudyantara (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Along with the times, many new MSMEs have emerged, where many people who have experienced termination of employment have flocked to open their own businesses to be able to survive in the midst of the Covid-19 pandemic outbreak that hit. With the emergence of new MSMEs, old MSMEs are increasingly aggressive in competing in the trade market. Many factors influence the application of digitalization in business management for MSME actors. This study used a quantitative approach with a total sample of 20. The results of the research obtained are: 1) Factors of technological progress affect the application of digitalization in business management for MSME actors. 2) The factor of the desire of MSME owners to advance their business affects the application of digitalization in business management for MSME actors. 3) The desire to accelerate services to the implementation of digitalization in business management for MSME actors. 4) The factor of facilitating services and transactions to the application of digitalization in business management for MSME actors. 5) Factors of technological progress, factors of the desire of MSME owners to advance the business, factors of wanting to speed up services, factors of facilitating services and transactions to the application of digitalization in business management for MSME actors. The desire to speed up service factor was the factor that had the most influence in this study compared to other factors